Oxidative Stress and Its Association with COVID-19: A Narrative Review - Baqi, Hardi Rafat; M. Farag, Halgord Ali; El Bilbeisi, Abdel Hamid H.; Askandar, Rafee Habib; El Afifi, Amany M. (Kurdistan Journal of Applied Research, 2020)
The naturalness of severe acute respiratory syndrome coronavirus 2 infections (SARS-Cov-2) appears to impact the respiratory system and lungs, however, the etiology of many cases exhibited several various features of the disease. The Coronavirus disease 2019 (COVID-19) symptoms are not limited to the virus’s first definitions. This review gathered the contemporary information throughout PubMed, Scopus, and Science Direct databases regarding possible effects of the virus in generating reactive oxygen species and causing oxidative stress. However, this ensures a hypothesis for now, yet from the literature and incidence of COVID-19 symptoms along with comorbidities we can observe the potentials of the virus in the generation of oxidative stress. Especially the virus’s route to cell entry via angiotensin-converting enzyme 2 (ACE2) receptor is well known that leads to pathogenesis in angiotensin II (AT II) which are critical in NADH/NADPH oxidase inducing ROS generation. Moreover, the virus’s activity to replicate seems to be reduced in high antioxidant glutathione level concentrations. The outcome of the review proposes a hypothesis that COVID-19 is associated with reactive oxygen species and its comorbidities mostly joined with oxidative stress including hypertension, cardiovascular, thrombosis, obesity, and diabetes besides of chronic obstructive pulmonary disease and asthma.